2020
DOI: 10.1063/1.5140772
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning methods for super-resolution reconstruction of turbulent flows

Abstract: Two deep learning (DL) models addressing the super-resolution (SR) reconstruction of turbulent flows from low-resolution coarse flow field data are developed. One is the static convolutional neural network (SCNN), and the other is the novel multiple temporal paths convolutional neural network (MTPC). The SCNN model takes instantaneous snapshots as an input, while the MTPC model takes a time series of velocity fields as an input, and it includes spatial and temporal information simultaneously. Three temporal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(94 citation statements)
references
References 25 publications
0
93
0
1
Order By: Relevance
“…2019 a , b ; Kim & Lee 2020 b ; Liu et al. 2020; Scherl et al. 2020), might be inevitable consequences of minimizing the pointwise error against the target data because the given information is insufficient to determine the solution uniquely and the target is only one of the possible solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2019 a , b ; Kim & Lee 2020 b ; Liu et al. 2020; Scherl et al. 2020), might be inevitable consequences of minimizing the pointwise error against the target data because the given information is insufficient to determine the solution uniquely and the target is only one of the possible solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Fukami, Fukagata & Taira (2019 a , 2020 b ) and Liu et al. (2020) reconstructed a flow field from a low-resolution filtered field using a convolutional NN (CNN). The method shows significant potential.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that high-resolution two-dimensional turbulent flow fields of a 128 × 128 grid can be reconstructed from the input data on a coarse 4 × 4 grid via machine learning methods. Applications and extensions of SR reconstruction can be considered for not only computational (Onishi, Sugiyama & Matsuda 2019;Liu et al 2020) but also experimental fluid dynamics (Deng et al 2019;Morimoto, Fukami & Fukagata 2020). Although these attempts showed great potential of machine-learning-based SR methods to handle high-resolved fluid big data efficiently, their applicability has been so far limited only to two-dimensional spatial reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Applications and extensions of SR reconstruction can be considered for not only computational (Onishi, Sugiyama & Matsuda 2019; Liu et al. 2020) but also experimental fluid dynamics (Deng et al. 2019; Morimoto, Fukami & Fukagata 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fukami et al [124] adopted the CNNs and the hybrid Downsampled Skip-Connection Multi-Scale (DSC/MS) models to perform super-resolution and temporal continuity analysis to reconstruct the high-resolution turbulent flow field based on only 50 training data. Liu et al [125] proposed a novel multiple temporal paths convolutional neural network (MTPC). The MTPC model takes a time series of velocity fields as input.…”
Section: B Unsteady Flow Field Reconstructionsmentioning
confidence: 99%